2015
DOI: 10.1186/s12882-015-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography in chronic kidney disease: a pilot experience in native kidneys

Abstract: BackgroundThere currently is a need for a non-invasive measure of renal fibrosis. We aim to explore whether shear wave elastography (SWE)-derived estimates of tissue stiffness may serve as a non-invasive biomarker that can distinguish normal and abnormal renal parenchymal tissue.MethodsParticipants with CKD (by estimated GFR) and healthy volunteers underwent SWE. Renal elasticity was estimated as Young’s modulus (YM) in kilopascals (kPa). Univariate Wilcoxon rank-sum tests were used.ResultsTwenty-five particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 39 publications
3
110
5
Order By: Relevance
“…Of the few studies that examined the use of SWE to assess renal stiffness, and its relationship to native kidney function, four evaluated renal elasticity in CKD patients 8,3840. Only two studies showed that SWE imaging, using ARFI-based technology, can be used to assess renal morphologic changes in patients with DKD 10,11.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few studies that examined the use of SWE to assess renal stiffness, and its relationship to native kidney function, four evaluated renal elasticity in CKD patients 8,3840. Only two studies showed that SWE imaging, using ARFI-based technology, can be used to assess renal morphologic changes in patients with DKD 10,11.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the elastic modulus of an underlying surface can modulate cell migration (5)(6)(7)(8), cell differentiation (9-13), cell spreading (14,15), and cell survival (16)(17)(18). Clinical studies have shown that tissue stiffness can have profound effects on disease progression: patients bearing malignant tumors with increased elastic modulus present with more severe disease (19,20); increased elastic modulus in liver tissue is a predictor of cirrhosis (21); and kidney tissue stiffness has been shown to correlate with disease progression in chronic kidney disease (22). Clearly, cells are able to sense the mechanical properties of their surroundings, and subsequent cell fate and function are determined by mechanically transduced signals.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements taken so far have significant variations between studies, highlighting the necessity for extensive trials on healthy kidneys. For example, the elasticity values of renal cortex varies, upon different assessments, between 15.4±2.5 kPa [18] to 5.0±2.9 kPa [21] or even 4.40 (3.68, 5.70) kPa [32] for Young's modulus in SSI or SWEI, and between 1.75 m/s [25] to 2.54±0.83 m/s [27] for shear wave velocity in ARFI. The kidney region examined is important, as significant differences in elasticity have been reported between the outer and inner cortex [22], between the medullary and cortical portion of the kidney [18], and between the cortex and renal pelvis [21].…”
Section: Evaluating Fibrosis In Native Kidney With Us Elastographymentioning
confidence: 99%
“…In the native kidney, human studies have reported various markers associated with increased kidney stiffness: estimated glomerular filtrate rate (eGFR) [23,28,29], urinary albumin / creatinine or protein / creatinine ratio [30,33], serum creatinine [23,29], urea nitrogen [23], elasticity values in healthy native kidneys [23][24][25][26][27][28][29][30][31][32][33]35], kidney biopsies [25], other imaging tests etc [24,26,35]. Thus, there are studies finding no significant correlation between markers of chronic kidney injury and elasticity of renal parenchyma in native [27] or transplanted kidney [48,51], and also studies which could not prove a significant difference of elasticity between different stages of CKD [23,25]; in addition, it has been reported an increased intra-subject variability of results in CKD versus healthy controls [33] or a higher influence of arteriosclerosis markers, such as pulsatility index or resistivity index, on kidney stiffness than eGFR [28].…”
Section: Evaluating Fibrosis In Native Kidney With Us Elastographymentioning
confidence: 99%